RANCANG BANGUN ANTENA ARRAY MIKROSTRIP DENGAN FREKUENSI 2,4 GHZ SEBAGAI TRANSCEIVER PENGUATAN SINYAL WIFI ADAPTER - ., Asep Syaiful Rohman (Faculty of Engineering, Universitas Tanjungpura, 2018)
Microstip antenna widely applied in the world of telecommunications. This is because the microstrip antenna has several advantages when compared to other types of antennas, such as it has a low profile form (thin and small), has a light weigt, easily fabricated, and the price is relatively cheaper. But the microstrip antenna also has some disadvantages, those are low gain, low bandwidth, low efficiency, and surface waves. In this final project it has been designed of equilateral triangle with 4 elements microstrip array antenna as reinforcement of wifi adapter transceiver. Microstrip array antenna design formed by a equilateral triangle radiator patch with T-junction channel. Basic media of this antenna design was using substrates made form Fiberglass Efoxy FR-4 with 1,6 mm substrat thickness and dielectric constant 4,4. The triangle patch form based on theoritical analysis of cavity model frequency 2,4 GHz. Parameter that must be consedered in the design of the antenna as LAN wireless such as working frequency, input impedance, and SWR (Standing Wave Ratio). This microstrip array antenna has input impedance parameter values 4,8952+ J 1,2238 Ohm, SWR1,6432. This microstrip antenna testing includes testing the connectivity using CMD available on PC with windows operating system, testing the download and upload speed using Speedtest.net, and more imfortant than this thesis is the testing of antenna transmit power by using Vistumbler software. As for the result of differences in the transmit power received by the divice has a minimum difference of 0 dBm and -5 dBm maximum difference. Key Word : Antenna Microstrip, Transceiver, Wifi Adapter, Low Profile, Array